Censorship of the Polish Periodical Press in Vilnius in the Years 1905–1914 - Mastianica, Olga (Knygotyra, 2023)
The article is devoted to the policy of censorship in Lithuania after the Manifesto issued by Emperor Nicholas II on 17 October 1905 in order to find out those ideas, thoughts, and opinions that the authorities of the Russian Empire sought to exclude from the communication process. The main object of the research is the Polish periodical press (newspapers, magazines, continuous, and one-off publications) published in Vilnius in 1905-1914. With the help of a comparative perspective, we will try to answer the question of whether the censorship of the Polish periodicals was subject to the same policy as other publications, whether there were peculiarities, or whether these periodicals were addressed more strictly. The main source of the research is the materials of the minutes of the meetings of the Temporary Committee on Press Affairs in Vilnius that have not been used in previous research.